Water harvesting for restoring rangelands in Jordan. - Strohmeier, Stefan (2017)
Optimizing mechanized micro water harvesting technique can help restore degraded rangelands in Jordan, a research using Rangeland Hydrology and Erosion Model suggests. Population growth, refugee movement, and boundary restrictions affect the livelihoods of nomadic communities and increase pressures on fragile rangelands throughout the Middle East, including Jordan's Badia. Overgrazing, caused by an increase in livestock herds degrades native vegetation and harms the soils, which leads to decreased rainwater infiltration and retention capacity, accelerating surface runoff and erosion.